Exploration and Process Optimization of Mixed Crystal Reasons in Steel SCR420H for Cold Forging Three-pins Shaft - Zhang Xuecheng, Yao Hailong, Li Zhongping (Teshugang)
The wire cutting and corrosion of the three-pins shaft part were carried out， and the microstructure observation results showed that there was severe mixed crystal phenomenon in the area with the highest cold deformation rate of the three-pins shaft head. Through in-depth exploration of this phenomenon， it was analyzed that the reason for mixed crystals in this area is due to the significant deformation experienced on both sides of the shaft head during the cold extrusion process of the three-pins shaft. During the high-temperature carburizing process， small grains fused with each other， ultimately forming coarse grains. In order to eliminate coarse grains on both sides of the shaft head of the three pin shaft component， different normalizing and annealing pretreatment processes were adopted to cause a large amount of AlN compounds in the material to precipitate again and form segregation at the grain boundaries， forming new AlN precipitates that play a strong role in pinning the grain boundaries. The normalizing and annealing pretreatment processes with different process parameters can improve the austenite grain size of the three-pins shaft parts to varying degrees. The best pretreatment scheme for improving the effect is the pre normalizing process above 900 ℃. The adoption of this scheme can improve the grain size of the three-pins shaft parts that were originally severely mixed， and the grain size of the three-pins shaft parts can reach 7.0 or above.